Portable pit latrine seats to increase sanitation for disabled individuals in Lira, Uganda - Mei-Li Hey; Harrison Schmachtenberger; Mikaya LD Lumori (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2022)
This paper presents a viable solution that evolved over several years of research to mitigate the sanitation problems faced by individuals in rural areas of Uganda, particularly those with disabilities, addressed in our first paper (Schmachtenberger et al.). The solution is based on interviews and contacts with affected individuals in Lira, Northern Uganda, where the most commonly used sanitation facility is a pit latrine. To that end three types of design considerations and requirements for effective pit latrine assistive devices were adopted in the development of the technology discussed in this paper. Ultimately, three different designs were fabricated after synthesizing the requirements, preliminary user feedback, and engineering knowledge of mechanical design. The deliverables from these designs are three different assistive devices whose common feature is a portable seat that can be used safely in a pit latrine. The good results from several field tests engendered the development of more locally reproducible and cost-effective, assistive seat devices over a period of 3-5 years. Results from data collected over the years will be published in another manuscript, subsequently.